Rahsia menjadi kaya dan berjaya dunia dan akhirat - Hussien Alattas, Syed.; Azizan Osman, 1974- ([Gombak, Kuala Lumpur] : JB News Media Network, 2010)
Achieving wealth and success according to Islamic principles; with examples of personal success stories in Malaysia and other countries.
In Malay.
Keywords: Success -- Religious aspects -- Islam; Success; Successful people